Wound fluid under occlusive dressings from diabetic patients show an increased angiogenic response and fibroblast migration. Issue 3 (August 2021) - Cerny, Michael K.; Wiesmeier, Anna; Hopfner, Ursula; Topka, Charlotte; Zhang, Wen; Machens, Hans-Günther; van Griensven, Martijn; Broer, Niclas; Duscher, Dominik
Abstract: Introduction: Metabolic diseases like diabetes mellitus often show prolonged healing and chronic wounds. Occlusive wound dressings are known to support wound closure by creating a moist environment which supports collagen synthesis, epithelialization and angiogenesis. We aimed to assess the effect of occlusion on diabetic wound fluid on the cellular level regarding fibroblast activity and angiogenetic response. Material and methods: 22 split skin donor sites from 22 patients (11 patients with diabetes mellitus) were treated with occlusive dressings intraoperatively. On day 3, fluid and blood serum samples were harvested while changing the dressings. The influence of wound fluid on fibroblasts was assessed by measuring metabolic activity (Alamar Blue assay, Casey Counter), cell stress/death (LDH assay) and migration (in vitro wound healing assay) of fibroblasts. Angiogenesis of endothelial cells (HUVEC) was analyzed with the tube formation assay. Furthermore, a Magnetic Luminex Assay for multi-cytokines detection was performed focusing on inflammatory and pro-angiogenetic cytokines. Results: The influence of wound fluid under occlusive dressings from diabetic patients showed a significantly increased angiogenic response and fibroblast migration compared to the non-diabetic patient group. Additionally, cell stress was increased in the diabetic group. Cytokine analysis showed an increase in VEGF-A in the diabetic group. Conclusion: Occlusive dressings may stimulate regenerative effects in diabetic wounds. Our in-vitro study shows the influence of wound fluid under occlusive dressings from diabetic patients on angiogenesis, migration and proliferation of fibroblasts, which are essential modulators of wound healing and scar modulation. Highlights: Occlusive dressings (OD) may positively affect wound healing of diabetic patients. Wound fluid analysis showed an increased HS-27 Fibroblast migration in the diabetic group compared to the control. Cell cytotoxicity was increased in the diabetic group. The Tube Formation Assay showed in overall an increased angiogenesis in the diabetic group. Occlusive dressings may benefit patients with chronic wounds and diabetes to facilitate and promote wound healing.